2014
DOI: 10.1089/scd.2013.0308
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 Inhibits the Proliferation and Self-Renewal of Esophageal Cancer Stem-Like Cells by Suppressing Stem Renewal Factor Bmi-1

Abstract: Cancer stem-like cells exist in many malignancies and several stem cell-related genes and microRNAs, such as Bmi-1 and miR-203, have been identified as cancer stem-like cell regulators using gene microarray or sequencing analysis. Previously, we used side population (SP) sorting to enrich cancer stem-like cells from esophageal squamous cell carcinoma (ESCC) cell line EC9706. Our results demonstrated that EC9706 SP cells shared common features of cancer stem-like cells. In this study, we examined the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 40 publications
3
66
0
2
Order By: Relevance
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 90%
“…A previous study revealed that molecular markers of cancer stem-like cells were connected with malignancies by using gene microarray and sequencing analysis (9). Another study demonstrated that miRNAs are critical in the carcinogenesis of lung cancer (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also target Hakai and inhibit the growth of human colon adenocarcinoma (28). Additionally, those genes involved in the regulation of cell proliferation, apoptosis, cell cycle progression, migration and invasion, are also the targets of miR-203, including Robo1, Kif5b, E2F3, LASP1, ASAP1, PKCα, BIRC5, Bmi-1 and DeltaNp63 (23)(24)(25)(26)(29)(30)(31)(32)(33). Whether these miR-203 targets are also involved in the development and progression of NB remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The application of high-throughput sequencing and microarray technology has produced notable alterations in the miRNA expression profiles of tumor tissue, as compared with normal tissue (9,10). Variations in miRNA expression levels between tumor tissues and normal tissues may lead to the dysfunction of downstream signaling pathways, which are associated with proliferation, invasion, angiogenesis and the metastasis of tumors (11,12,13). Furthermore, miRNA molecules are highly stable, which facilitates their survival in tissue fluid, blood and urine (14).…”
Section: Introductionmentioning
confidence: 99%